Clinical outcomes of rescue stenting for failed endovascular thrombectomy: a multicenter prospective registry. (12th January 2022) - Baek, Jang-Hyun; Kim, Byung Moon; Ihm, Eun Hyun; Kim, Chang-Hyun; Kim, Dong Joon; Heo, Ji Hoe; Nam, Hyo Suk; Kim, Young Dae; Suh, Sangil; Kim, Byungjun; Won, Yoodong; Baek, Byung Hyun; et al.
Abstract : Background: Mechanical thrombectomy (MT) is a primary endovascular modality for acute intracranial large vessel occlusion. However, further treatment, such as rescue stenting, is occasionally necessary for refractory cases. We aimed to investigate the efficacy and safety of rescue stenting in first-line MT failure and to identify the clinical factors affecting its clinical outcome. Methods: A multicenter prospective registry was designed for this study. We enrolled consecutive patients who underwent rescue stenting for first-line MT failure. Endovascular details and outcomes, follow-up patency of the stented artery, and clinical outcomes were summarized and compared between the favorable and unfavorable outcome groups. Results: A total of 78 patients were included. Intracranial atherosclerotic stenosis was the most common etiology for rescue stenting (97.4%). Seventy-seven patients (98.7%) were successfully recanalized by rescue stenting. A favorable outcome was observed in 66.7% of patients. Symptomatic intracranial hemorrhage and mortality were observed in 5.1% and 4.0% of patients, respectively. The stented artery was patent in 82.1% of patients on follow-up angiography. In a multivariable analysis, a patent stent on follow-up angiography was an independent factor for a favorable outcome (OR 87.6; 95% CI 4.77 to 1608.9; p=0.003). Postprocedural intravenous maintenance of glycoprotein IIb/IIIa inhibitor was significantly associated with the follow-up patency of the stented artery (OR 5.72; 95% CI 1.45 to 22.6; p=0.013). Conclusions: In this multicenter prospective registry, rescue stenting for first-line MT failure was effective and safe. For a favorable outcome, follow-up patency of the stented artery was important, which was significantly associated with postprocedural maintenance of glycoprotein IIb/IIIa inhibitors.